Risk factors for cystocele, rectocele, and uterine prolapsed in women. Iran, Tehran - Mokhtarshahi Sh (Iran University of Medical Sciences, 1999)
This is a case-control study. The purpose was to investigate for risk factors for cystocele, rectocele, and uterine prolapsed in women. The sample was 249 women who refereed to a gynecological clinic. Of them 155 women placed in case and 84 women placed in control group. The tool for data gathering was a questionnaire which was designed in three parts. The first part was demographic characteristics the second was 23 questions about personal, gestational, and parturitional, risk factors, and the third part was recorded information due to direct observation and examination of women. Results showed that most women in case group were 30-39 years old and with lighter skin. In opposite most women in control group were 20-29 years old and were swarthy. Prevalence of genital prolapsed was 64.85 percent. Some of personal risk factors were duration of labor, weight of newborn, and the manner of initiation of labor. There were relationship between constipation with rectocele and between compression incontinency with cystocele, but there were no relationship between gestational and parturitional risk factors with vaginal prolapsed.